Orthopaedic Surgeon Communication Skills: Perception of Empathy and Patient Satisfaction Through the Use of Anatomic Models. (November 2018) - Portalatín, Edwin L.; Carrazana, Luis F.; Colon, Roberto; Abreu, Ricardo; Rivera, Dennys; Lojo, Luis
Abstract : Introduction: Patient satisfaction is an increasingly emphasized measure of patient-centered care and important component of reimbursement programs. Orthopaedic surgeons are regarded as low-empathy surgeons. Our goals were to understand the role of anatomic models during the orthopaedic appointment and how their use can affect patient satisfaction and perceived empathy. Methods: New patients at an outpatient clinic were asked to participate in a postencounter questionnaire to asses empathy perception (n = 304). Clinic days were randomly assigned to use anatomic models during the encounter to assist with clinical information transmission. The instrument provided contained Consultation and Relational Empathy questionnaire (ie, a person-centered process that was developed to measure empathy in the context of the therapeutic relationship during a one-on-one consultation between a clinician and a patient). Results: A total of 304 participants were included in the study. Analyses of the sociodemographic characteristics did not reveal any significant difference between the control and experimental groups. Consultation and Relational Empathy scores for the nonanatomic group (46.0 ± 9.0) and anatomic group (48.0 ± 7.7) were not statistically different ( P = 0.482). The encounter time was significantly increased with the use of anatomic models ( P < 0.005). Discussion: The use of anatomic models during initial orthopaedic encounter did not improve perceived empathy and satisfaction scores in our study. Longer encounter time in the orthopaedic appointment does not mean higher empathy perception. Conclusion: Orthopaedic surgeons have the duty to find new strategies to improve communication with the patient. Better communication has been associated with better patient satisfaction. Further investigation should be considered to use other strategies to provide better care for our patients.